Representaciones gráficas de niños y niñas de preescolar, segundo y cuarto grado, con y sin necesidades educativas especiales - Rojas Rodríguez, Dinia (2006)
This research on the body parts concept held by children with and without special needs from preschool, second and fourth grade provides data about their graphic representations of body parts. In both groups, most students made accurate representations of their body image, but the drawings of one large group of students with special needs from all three grades show characteristics below those expected for children in their age range. Another small group of students with and without special needs from preschool and second grade made drawings with characteristics beyond those expected for their age. We suggest that all educational processes take into account students’ previous knowledge and emphasize not only the teaching of body-related concepts but also concepts related to body image. Teaching activities must also allow students to experience and construct the studied concepts.